Relation of Phytochrome-enhanced Geotropic Sensitivity to Ethylene Production - Kang, Bin G. (1972)
Brief exposure of etiolated pea (Pisum sativum cv. Alaska) seedlings to red light enhances subsequent development of geotropic curvature of the stem. Both this response and inhibition of ethylene production by red light become maximal 8 hours after illumination. Very low concentrations of applied ethylene inhibit development of geotropic curvature, whereas hypobaric treatment enhances geotropic sensitivity by removing endogenous ethylene. Increased geotropic sensitivity after illumination is accompanied by increased lateral migration of (3)H-indoleacetic acid in response to gravity, and ethylene inhibits this lateral migration. It is suggested, therefore, that red light-enhanced geotropic sensitivity is caused by increased lateral auxin transport resulting from a reduction in ethylene production after illumination.